The Psychological Impact of Divorce on Children in Manado City, North Sulawesi - Ardianto, Ardianto; Gunawan, Edi; Yusuf, Nasruddin; Tubagus, Munir (Universitas Islam Sultan Agung, 2023)
Divorce is a complex life event that often has significant impacts, especially on the psychological well-being of children. This research aims to deeply explore the psychological impact of divorce on children in Manado City, North Sulawesi. Through a qualitative approach, we conducted in-depth interviews with 20 informants, including children, divorced parents, and judges from the Manado Religious Court. The results of the study indicate that divorce affects not only the physical and social aspects of children but also significantly impacts their emotional state. Children who are victims of their parents' divorce often experience deep feelings of loss, uncertainty about their family's future, and confusion about the causes of the divorce. Emotional conflicts also arise in children who are victims of divorce, such as feelings of guilt, anger, sadness, and prolonged anxiety. These psychological impacts are then reflected in various aspects of the child's life, including a decline in academic performance, lack of motivation to study, and deviant behaviors such as drug use or engaging in promiscuous activities. In facing these challenges, it is crucial for children to receive adequate social and psychological support. Therefore, the roles of family, government, schools, and the surrounding community in providing appropriate support and facilitating children's adaptation to their parents' divorce are very important. Support from various parties can help children who are victims of divorce in their psychological recovery.